Predicting Outcome of Inpatient CBT for Adolescents with Anxious‐Depressed School Absenteeism. (17th November 2011) - Walter, Daniel; Hautmann, Christopher; Minkus, Johannes; Petermann, Maike; Lehmkuhl, Gerd; Goertz‐Dorten, Anja; Doepfner, Manfred
<x xml:space="preserve">Abstract</x> Predictors of outcome of inpatient treatment based on manualized cognitive–behavioural therapy (CBT) were examined for 147 adolescents with anxious‐depressed school absenteeism assessed at discharge and at 2 months after the end of treatment. Outcome measures were regular school attendance and a wide variety of mental health problems rated by adolescents and parents. Socio‐demographic data, clinical ratings/diagnosis and adolescent‐reported and parent‐reported mental health problems were examined as predictors. Regression analyses indicated that none of the variables were able to predict regular school attendance in a clinically relevant way. Adolescent‐reported and parent‐reported mental health problems at intake predicted these symptoms at both discharge and follow‐up (R2 between 0.31 and 0.61). Copyright © 2011 John Wiley & Sons, Ltd. Key Practitioner Message When treating anxious‐depressed adolescents with chronic school absenteeism in an inpatient setting using CBT, socio‐demographic data, clinical ratings, diagnosis or self‐reported and parent‐reported mental health problems cannot predict treatment outcomes on school absenteeism. Even severely impaired adolescents do not necessarily have the worst outcome in terms of high school absence rates. Severity of self‐reported and parent‐reported mental health problems at the start of inpatient treatment using CBT best predict these symptoms at discharge and at 2 months after the end of inpatient treatment.